Development and Operation of a Global‐Scale Seismographic Network: The IRIS/USGS GSN - Peter Davis (Perspectives of Earth and Space Scientists)
Abstract From inception in the late 1980s up to the present, the Global Seismographic Network has produced high quality seismic data that has advanced research into the structure of the Earth's deep interior particularly the large‐scale heterogeneous elastic/anelastic structure of the mantle and core. The network's breadth of coverage enables images of great earthquakes impossible to obtain from regional networks or array data alone. Analysis of the data has provided new insights into non‐traditional seismic sources such as slow earthquakes, glaciers and landslides. Ancillary meteorological and infrasound sensors collocated at the sites support unique studies of volcanic events such as the recent eruption of the Hunga Tonga–Hunga Ha'apai volcano. Near real‐time transmission of the data to hazard warning centers has expanded the network's usefulness as a tool for rapid response to earthquakes, for warning communities effected by tsunamis, and for monitoring compliance with nuclear test ban treaties. The successful construction and operation of the network would not be possible without the outstanding international cooperation of many governmental, academic and private groups who have hosted components of the network.